2013
DOI: 10.1111/jvim.12164
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Efficacy of Mineral Oil, Charcoal, and Smectite in a Rat Model of Equine Cantharidin Toxicosis

Abstract: Background: The efficacy of orally administered therapeutics for the treatment of cantharidin intoxication has not been evaluated in controlled studies.Objective: To develop a model of acute cantharidin intoxication in laboratory rats and to evaluate in this model the relative efficacy of 3 gastrointestinal therapies used to treat equine cantharidin toxicosis.Animals: Sixty-four male Sprague-Dawley rats. Methods: A blinded, randomized, controlled study was performed on rats surgically implanted with telemetry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…In conclusion, the present study revealed that the charcoal-treated group showed enhancement in both epithelial and connective tissue architecture of the tongue, mucous and serous acini, which might be due to the protective action of charcoal in the treatment of toxicosis. Activated charcoal adsorbs ingested toxins within the gastrointestinal tract hindering the systemic absorption of that toxin [13,16]. Moreover, our observations suggest that the degenerative effects of tacrolimus were temporary.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In conclusion, the present study revealed that the charcoal-treated group showed enhancement in both epithelial and connective tissue architecture of the tongue, mucous and serous acini, which might be due to the protective action of charcoal in the treatment of toxicosis. Activated charcoal adsorbs ingested toxins within the gastrointestinal tract hindering the systemic absorption of that toxin [13,16]. Moreover, our observations suggest that the degenerative effects of tacrolimus were temporary.…”
Section: Discussionmentioning
confidence: 77%
“…Additionally, TAC has induced mucosal pigmentation on topical application [12]. Oral administration of activated charcoal (AC) has been evident in treating the side effects of immunosuppressants and many drug-induced toxicoses [13,14]. Production of AC commences by heating bamboo or wood and proceeds by its conversion into powder with micro-porosities to increase its surface area, attaining absorbent properties to the charcoal [15].…”
Section: Introductionmentioning
confidence: 99%